2006
DOI: 10.1038/sj.ejcn.1602502
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of serum cobalamins and its binding proteins in lactating women

Abstract: Objective: To examine longitudinal changes in serum cobalamins, transcobalamin (TC) and haptocorrin (HC) during lactation and to investigate the influence of vitamin B 12 supplementation on these parameters. Design: A 9-month follow-up study. Subjects and methods: Lactating mothers (N ¼ 89) including 23 supplemented with vitamin B 12 (1-18 mg/daily), 41 partly supplemented and 25 not supplemented. Blood samples collected 3 weeks (baseline) and 4 and 9 months post-partum were analysed for cobalamins, TC and HC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In a subgroup of 25 mothers, a decline in breast milk cobalamin concentration was observed between two weeks and four months post partum followed by an increase at nine months post partum (Section 2.3.6.2). In a longitudinal study in 89 Danish lactating women, most of whom reported to take cobalamin supplements (1-18 μg/day, median 1 μg/day), no change in serum cobalamin concentration was observed from three weeks to nine months post partum, whereas a significant decrease in serum holoTC and an increase in haptocorrin concentrations were reported (Mørkbak et al, 2007a). Serum cobalamin, holoTC and haptocorrin concentrations after nine months showed no statistical difference between the supplemented (n = 23) and unsupplemented (n = 25) mothers.…”
Section: Lactating Womenmentioning
confidence: 95%
“…In a subgroup of 25 mothers, a decline in breast milk cobalamin concentration was observed between two weeks and four months post partum followed by an increase at nine months post partum (Section 2.3.6.2). In a longitudinal study in 89 Danish lactating women, most of whom reported to take cobalamin supplements (1-18 μg/day, median 1 μg/day), no change in serum cobalamin concentration was observed from three weeks to nine months post partum, whereas a significant decrease in serum holoTC and an increase in haptocorrin concentrations were reported (Mørkbak et al, 2007a). Serum cobalamin, holoTC and haptocorrin concentrations after nine months showed no statistical difference between the supplemented (n = 23) and unsupplemented (n = 25) mothers.…”
Section: Lactating Womenmentioning
confidence: 95%
“…Holo-and total HC were measured as described previously (21,22). Total cobalamins were analysed employing an Advia Centaur (Bayer A/S, Leverkusen, Germany) and holoTC was analysed by an in-house ELISA (23).…”
Section: Data Included For Analysing the Relation Between Vitamin B 1mentioning
confidence: 99%
“…Infantile vitamin B-12 deficiency can lead to neurologic impairments including irritability, apathy, and developmental regression (16)(17)(18). Although a few studies have examined longitudinal changes in maternal vitamin B-12 biomarkers during lactation (14,(19)(20)(21), less is known about the impact of this reproductive state (compared to the nonlactating state) on vitamin B-12 status and requirement.…”
Section: Introductionmentioning
confidence: 99%